Aplikasi Quizizz Sebagai Media Pembelajaran Pendidikan Agama Islam (PAI) - Munawaroh, Faikhatul; Muhammada, Muhammada; Yusuf, Achmad (JOEAI (Journal of Education and Instruction), 2023)
Abstract: All information about the formatting requirements is contained Educators must have a lot of creative and innovative ideas in creating interesting and fun learning. Selection of appropriate learning media is one of the important things to support the success of education. The quizizz application is an interactive learning media that implements a "learning while playing" system. The use of the quizizz application can be used as a learning medium, especially in presenting quizzes to students that are easily accessible via smartphones, so that the young generation's closeness to smartphones can be utilized optimally and positively. This study aims to determine the implementation of the quizizz application in Islamic education (PAI) subjects at SMAN 1 Gondangwetan along with its supporting and inhibiting factors. This study employs descriptive qualitative methodology. Observational, interview-based, and document-based data collection techniques. The results of the study indicate that the implementation of the quizizz application in Islamic education (PAI) courses is highly suitable as a learning medium because it makes the learning process interactive, enjoyable, simple for students to comprehend, and simpler for educators to track student learning outcomes. Keywords: implementation, learning media, quizizz, islamic education